Determinants of Competitor Response Time to a New Product Introduction - Bowman, Douglas; Gatignon, Hubert (Journal of Marketing Research, 1995)
This research studies a neglected dimension of competitive defensive strategy—the speed of a competitor's reaction to the introduction of a new product. Building on the literature in organizational and strategic management, the authors investigate how the strategic pressures facing a firm and its organizational characteristics influence the speed with which it is willing and able to respond. A model that considers the ordered nature of the dependent measure is specified and estimated using PIMS data on industrial and consumer product manufacturers. Market growth, the market share of the reacting firm, the typical new product development time and the frequency of product changes in the industry, and the market share of the threatening firm appear to be significant determinants of reaction time.